Total Adiponectin Is Inversely Associated with Platelet Activation and CHA2DS2-VASc Score in Anticoagulated Patients with Atrial Fibrillation - Roberto Carnevale; Daniele Pastori; Mariangela Peruzzi; Elena De Falco; Isotta Chimenti; Giuseppe Biondi-Zoccai; Ernesto Greco; Antonino G. M. Marullo; Cristina Nocella; Francesco Violi; Pasquale Pignatelli; Camilla Calvieri; et al. (Mediators of Inflammation)
Background. Adiponectin (APN) possesses anti-inflammatory and antiatherogenic effects. Atrial fibrillation (AF) is burdened by enhanced systemic inflammation and platelet activation, as documented by increased blood levels of soluble CD40L (sCD40L). The interplay between APN and platelet activation in AF is still undefined. Materials and Methods. Circulating levels of APN and sCD40L were measured in 257 anticoagulated nonvalvular AF patients. Exclusion criteria were as follows: prosthetic heart valves, cardiac revascularization in the previous year, severe cognitive impairment, chronic infectious or autoimmune diseases, and active cancer. Results. Mean age was 72.9 (±8.7) years and 41.6% were female. Serum APN and plasmatic sCD40L were inversely correlated (R −0.626, P<0.001). A progressive increase of sCD40L across tertiles of CHA2DS2-VASc score was observed (rS 0.473, P<0.001), whilst APN was inversely correlated (rS −0.463,  P<0.001). A multivariable linear regression analysis showed that CHA2DS2-VASc score (B −0.227, P<0.001) and sCD40L (B −0.524, P<0.001) correlated to APN. Conclusions. AF patients at high risk of stroke disclose low and high levels of APN and sCD40L, respectively, suggesting a role for APN if it favors platelet activation in vivo in this clinical setting. Enhancing APN levels may be a future goal to reduce the risk of vascular outcomes in AF patients.